Paraquat (methyl viologen) toxicity in centella asiatica callus cultures - Mohd Fadzillah, Nor'Aini; Yusuf, Norhayati; Mahmood, Maziah; Kusnan, Misri (Universiti Putra Malaysia Press, 2006)
The effect ofparaquat (PQ) treatment on growth, cell viability, hydrogen peroxide (H202) and malondialdehyde (MDA) levels were investigated in the callus of two Centella asiatica accessions (CA03 and CA09). Callus of C. asiatica were treated with 50l1M PQforfive days in Murashige and Skoog (MS) liquid medium. Callus growth, viability ofthe callus as well as H202 content and MDA levels were evaluated at 0, 1, 2,3 and 5 days oftreatment periods. Fresh weight and dry weight of treated calli were significantly lower in CA03 as compared to the untreated calli. In CA09, the growth of treated calli was significantly lower compared to controls at the later stages ofthe treatment period. Although decreases in growth were observedfor both treated CA03 and CA09, thefinal reduction in fresh weight at 36%for CA09 compared to its control was much higher compared to CA03 with an 18.2% final reduction in fresh weight. PQ treatment also resulted in a marked decrease in the viability of the callus especially in CA09. Although MDA levels were significantly higher in treated CA03 as compared to treated CA09 at the early treatment stages, they showed a decreasing trend, while MDA levels in CA09 showed an increasing trend, which was significantly higher than that of CA03 at the end of the treatment period. In addition, H202 concentrations were generally higher in treated CA09 compared to treated CA03 except at day 3. This study indicated that PQ treatment can induce increases in levels of MDA and H202, associated with the decrease in growth and viability ofthe callus. Results also suggested that CA03 was more tolerant to PQ treatment as compared to CA09.